On the Acquisition of Life Management Skills: A Reaction to the Position Paper on School Guidance Services - France, M. Honoré (Canadian Journal of Counselling and Psychotherapy, 2012)
This article is a personal response to the position paper of the Canadian School Trustees' Association (1981) on school guidance services. The author supports the notion that life management skills should be an important component of the school curriculum, with the addition of the practical competencies of change and adaptability.